Pocket-Picking to Armed Robbery to Prison: The Life and Criminological Analysis of Good Boy, Bad Boy and Wiser Man, Sal Ali - J Forbes Farmer; Sal Ali; Jean Dawson (Journal of Sociological Research, 2024)
This case study examines the self-reported life story of a prisoner who has spent much of his life in juvenile detention and adult prison. His criminal history began with pocket-picking, then breaking and entry, and then advanced to armed robbery. Social learning theory, self-control theory and rational choice theory are discussed and the inmate’s reflections on them are offered in his words with illustrations from his experience.